Gothic Fault-Lines in Anne Brontë’s Social Fiction: The Case of The Tenant of Wildfell Hall (1848) - Isabelle Hervouet (Cahiers Victoriens et Edouardiens)
The Tenant of Wildfell Hall (1848), Anne Brontë’s second novel, has always been the object of much scholarly attention, particularly as regards what was originally thought to be a structural flaw: the use of a frame narrative within which the story of Helen Huntingdon’s flight from a disastrous marriage is embedded. The frame narrator, Gilbert Markham, tells a traditional courtship tale which abruptly turns into Helen’s metanarrative of domestic horror. Recent scholarship has concerned itself with this split in discourse which suggests that Brontë does not challenge the conventional idea that discursive authority is masculine, making it therefore difficult to read her novel as feminist. Studies alternately focus on Brontë’s bold enterprise (the vindication in the metanarrative of a woman’s right to leave an abusive husband) or on the limitations generated by her decision to resort to a male frame narrator. This paper addresses the implications of the novel’s apparently flawed structure, notably exploring the uncertainty surrounding the improvement of Gilbert’s moral character after his reading of Helen’s diary. It contends that critical disagreement on whether or not The Tenant is a feminist novel and the embedded narrative the instrument of Gilbert’s reformation, originates, at least partially, in the generic tension at work within Brontë’s novel, and the presence of Gothic fault-lines. Anne Brontë appears unwilling to espouse realism and social criticism which, if fully embraced, might imply forgoing valued (and cherished) Gothic modes of storytelling. The uneasy co-existence of social realism and Gothic remnants (prominent in the choice of structure and modes of characterisation) may then lie at the heart of the novel’s multi-faceted ambiguity.